Looking for reliable answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Connect with a community of experts ready to help you find accurate solutions to your questions quickly and efficiently. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Answer
z= 14
Step-by-step explanation:
4( 2z-3) -5(z-6) =3 *20
8z-12-5z+30=60
3z+18=60
3z=60-18
3z=42
z= 14
[tex] \frac{2z - 3}{5} - \frac{z - 6}{4} = 3 \\ = > \frac{4(2z - 3) - 5(z - 6)}{20} = 3 \\ = > \frac{8z - 12 - 5z + 30}{20} = 3 \\ = > \frac{3z + 18}{20} = 3 \\ = > 3z + 18 = 3 \times 20 \\ = > 3z + 18 = 60 \\ = > 3z = 60 - 18 \\ = > 3z = 42 \\ = > z = \frac{42}{3} \\ = > z = 14[/tex]
Answer:
z = 14
Hope you could get an idea from here.
Doubt clarification - use comment section.
We appreciate your time. Please come back anytime for the latest information and answers to your questions. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.